Selection for high and low virulence in the malaria parasite Plasmodium chabaudi. - Mackinnon, M; Read, A (1999)
What stops parasites becoming ever more virulent? Conventional wisdom and most parasite-centred models of the evolution of virulence suppose that risk of host (and, hence, parasite) death imposes selection against more virulent strains. Here we selected for high and low virulence within each of two clones of the rodent malaria parasite Plasmodium chabaudi on the basis of between-host differences in a surrogate measure of virulence--loss of live weight post-infection. Despite imposing strong selection for low virulence which mimicked 50-75% host mortality, the low virulence lines increased in virulence as much as the high virulence lines. Thus, artificial selection on between-host differences in virulence was unable to counteract natural selection for increased virulence caused by within-host selection processes. The parasite's asexual replication rate and number of sexual transmission forms also increased in all lines, consistent with evolutionary models explaining high virulence. An upper bound to virulence, though not the asexual replication rate, was apparent, but this bound was not imposed by host mortality. Thus, we found evidence of the factors assumed to drive evolution of increased virulence, but not those thought to counter this selection.